Catherine Ceniza Choy. Global Families: A History of Asian International Adoption in America. New York: New York University Press, 2013. 229 pp. - Navallo, Katrina (Archīum Ateneo, 2015)
Excerpt: Perhaps one of the more popular, contemporary images of international adoption is that of Angelina Jolie’s family of six kids, three of whom are adoptees from Cambodia, Vietnam, and Ethiopia. Their story foregrounds the phenomenon of international adoption through the framework of global family making, which, as defined by Catherine Choy in her new book, Global Families: A History of Asian International Adoption in America, involves “the decisions made and actions taken by people who create and sustain a family by consciously crossing national and often racial borders” (9). Choy explores the historical background of international adoption in the United States and uncovers a multifaceted phenomenon that looks beyond US foreign relations and cultural imperialism to include a broader and deeper understanding of how migration, race, global family making, identity making, and intimacy converge to shape the dynamics of international adoption.